Dynamics of voluntary knowledge sharing in organizations - Suleman Aziz Lodhi; Munir Ahmad (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2010)
Knowledge has become prime source of economic production in modern enterprises; conceptualized by many researchers as the only source of sustainable competitive advantage. Therefore many organizations are restructuring themselves to gain maximum value from their knowledge sources. The paper investigates the influence of management policies on voluntary knowledge sharing behaviors at individual and group level and presents a model to understand the dynamics of voluntary knowledge sharing by employees in an organization. The problem is approached with a tacit view of knowledge, considering that true knowledge is located only in the minds of the professionals working in the organization.
Keywords: 330; Voluntary Knowledge Sharing; Knowledge Management; Organizational Knowledge; Organizational Learning; Communities of Practice; Knowledge Networks